Effect of the adjuvanted (AS03) A/H1N1 2009 pandemic influenza vaccine on the risk of rejection in solid organ transplant recipients in England: a self-controlled case series. Issue 1 (28th January 2016) - Cohet, Catherine; Haguinet, François; Dos Santos, Gaël; Webb, Dave; Logie, John; LC Ferreira, Germano; Rosillon, Dominique; Shinde, Vivek
Abstract : Objective: To assess the risk of solid organ transplant (SOT) rejection after vaccination with the adjuvanted (AS03) A/H1N1 2009 pandemic influenza vaccine Pandemrix . Design: Self-controlled case series (SCCS) in the UK Clinical Practice Research Datalink (CPRD) and its linked component of the Hospital Episodes Statistics (HES) inpatient database. Analyses were conducted using the SCCS method for censored, perturbed or curtailed post-event exposure. Participants: Of the 184 transplant recipients having experienced at least one SOT rejection (liver, kidney, lung, heart or pancreas) during the study period from 1 October 2009 to 31 October 2010, 91 participants were included in the main analysis, of which 71 had been exposed to Pandemrix . Main outcome measures: Occurrence of SOT rejection during risk (30 and 60 days after any Pandemrix dose) and control periods. Covariates in the CPRD included time since transplantation, seasonal influenza vaccination, bacterial and viral infections, previous SOT rejections and malignancies. Results: The relative incidence (RI) of rejection of any one of the five transplanted organs, adjusted for time since transplantation, was 1.05 (95% CI 0.52 to 2.14) and 0.80 (95% CI 0.42 to 1.50) within 30 and 60 days after vaccination, respectively. Similar estimates were observed for rejection of a kidney only, the most commonly transplanted organ (RI within 30 days after vaccination: 0.85 (95% CI 0.38 to 1.90)). Across various models and sensitivity analyses, RI estimates remained stable and within a consistent range around 1.0. Conclusions: These results suggest a reassuring safety profile for Pandemrix with regard to the risk of rejection in SOT recipients in England and contribute to inform the benefit–risk of AS03-adjuvanted pandemic influenza vaccines in transplanted patients in the event of future pandemics. Trial registration number: NCT01715792.